Investigations of Non-Covalent Carbon Tetrel Bonds by Computational Chemistry and Solid-State NMR Spectroscopy - Southern, Scott Alexander (Université d'Ottawa / University of Ottawa, 2016)
Non-covalent bonds are an important class of intermolecular interactions, which result in the ordering of atoms and molecules on the supramolecular scale. One such type of interaction is brought about by the bond formation between a region of positive electrostatic potential (σ-hole) interacts and a Lewis base. Previously, the halogen bond has been extensively studied as an example of a σ-hole interaction, where the halogen atom acts as the bond donor. Similarly, carbon, and the other tetrel elements can participate in σ-hole bonds. This thesis explores the nature of the carbon tetrel bond through the use of computational chemistry and solid state nuclear magnetic resonance (NMR) spectroscopy. The results of calculations of interaction energies and NMR parameters are reported for a series of model compounds exhibiting tetrel bonding from a methyl carbon to the oxygen and nitrogen atoms in a range of functional groups. The ¹³C chemical shift (𝛿iso) and the ¹ᶜ𝐽(¹³C,¹⁷O/¹⁵N) coupling across the tetrel bond are recorded as a function of geometry. The sensitivity of the NMR parameters to the non-covalent interaction is demonstrated via an increase in 𝛿iso and in |¹ᶜ𝐽(¹³C,¹⁷O/¹⁵N)| as the tetrel bond strengthens. There is no direct correlation between the NMR trends and the interaction energy curves; the energy minimum does not appear to correspond to a maximum or minimum chemical shift or J-coupling value. Gauge-including projector-augmented wave density functional theory (DFT) calculations of 𝛿iso are reported for crystals which exhibit tetrel bonding in the solid state. Experimental 𝛿iso values for sarcosine, betaine and caffeine and their tetrel-bonded salts generally corroborate the computational findings. This work offers new insights into tetrel bonding and facilitates the incorporation of tetrel bonds as restraints in NMR crystallographic structure refinement.
Keywords: Non-covalent Interaction; Tetrel Bonds; C-13 Chemical Shift; Sigma Hole; Solid-State NMR; Carbon Bonds; J-coupling